Calorie and nutrient gap analysis of jail menu and nutritional status of the prisoners of District Jail, Faisalabad, Pakistan - Arshad, Muhammad Bilal; Fahad Saleem; Rao Muhammad Haris (Journal of the Pakistan Medical Association, 2024)
Assessment of prisoners’ diet showed that it is deficient in calories as well as in Recommended Daily Allowance values. Caloric value was about 64.9% deficient considering one serving (plate per time) taken. A quantitative-qualitative mixed approach was adopted. Convenient purposive sampling was employed to recruit 112 participants. For quantitative assessment a descriptive cross-sectional study design and semi-structured data collection tool was used, and for qualitative evaluation, caloric and RDA value of different nutrients were calculated and in-depth interviews were conducted. Analysis showed that the diet provided was deficient in caloric and RDA values, thus the prison authority should design a proper strategy to ensure proper nutritional status of prisoners. Key words: Inmates, Prisoners, Servings, Associated factors, Mal-nutrition.